Managing Business Integrity : Prevent, Detect, and Investigate White-collar Crime and Corruption - Heissner, Stefan (Management for Professionals,, 2015)
This book deals with the highly complex but exciting subject of corporate fraud and corruption, which has since become the cops and robbers game of the 21st century: accounting fraud, embezzlement, bribery and many other forms of corruption and non-compliance cause turmoil between board members, supervisory board members and managers, while economic crime and corruption cause damages amounting to billions every year. When cases of misconduct and non-compliance become public knowledge, additional loss of reputation is the result, the consequences of which aren't even quantifiable for the companies concerned.   Written by one of the most accomplished corruption and compliance experts, Dr. Stefan Heissner, this book provides comprehensive information on the controversial aspects of combating fraud and corruption from their beginnings. It also offers amazing insights into current practices in the war on fraud and corruption - including some stunning findings.